(6x-5)(2-3x)=

Simple and best practice solution for (6x-5)(2-3x)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6x-5)(2-3x)= equation:


Simplifying
(6x + -5)(2 + -3x) = 0

Reorder the terms:
(-5 + 6x)(2 + -3x) = 0

Multiply (-5 + 6x) * (2 + -3x)
(-5(2 + -3x) + 6x * (2 + -3x)) = 0
((2 * -5 + -3x * -5) + 6x * (2 + -3x)) = 0
((-10 + 15x) + 6x * (2 + -3x)) = 0
(-10 + 15x + (2 * 6x + -3x * 6x)) = 0
(-10 + 15x + (12x + -18x2)) = 0

Combine like terms: 15x + 12x = 27x
(-10 + 27x + -18x2) = 0

Solving
-10 + 27x + -18x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-5 + 6x)(2 + -3x) = 0

Subproblem 1

Set the factor '(-5 + 6x)' equal to zero and attempt to solve: Simplifying -5 + 6x = 0 Solving -5 + 6x = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 6x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 6x = 0 + 5 6x = 0 + 5 Combine like terms: 0 + 5 = 5 6x = 5 Divide each side by '6'. x = 0.8333333333 Simplifying x = 0.8333333333

Subproblem 2

Set the factor '(2 + -3x)' equal to zero and attempt to solve: Simplifying 2 + -3x = 0 Solving 2 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3x = 0 + -2 -3x = 0 + -2 Combine like terms: 0 + -2 = -2 -3x = -2 Divide each side by '-3'. x = 0.6666666667 Simplifying x = 0.6666666667

Solution

x = {0.8333333333, 0.6666666667}

See similar equations:

| .073=x(.285) | | (216)^8/(6)^3 | | 5(8r+5)-5r=-31+7r | | (216)power8/(6power2)power3 | | 25-32= | | (216)^8/(6^2)^3 | | 162=6(7+4v) | | 2senx-3cotx=0 | | 2.5x/12x | | 155=5(-6a-5) | | -2+3y-8y+3x= | | 6-5n=-(n-6) | | 40r-5r+7r= | | (2x+5)=x+3 | | 4x(3x-1)-6(2x+1)= | | 3/10=-8/5-n | | 30/7x=-255/28 | | sec(2x)+tan(x)=1 | | a-(-16)=11 | | 5c^3-15c^2+10c=0 | | 3r+9=-3(8r-3) | | 3r+9=24+9 | | 7+15x+2x^2= | | log(5)(5x+6)=2 | | tanx=cotx | | 0.5r+7=9 | | -4c+4c-2= | | -5(7r+5)=31-7r | | 5x^2-2x-16=2x^2+6x | | 2cos(2x)-cos(x)=0 | | logx+2(0)16=4 | | 7r^2-19r-14=-3r+1 |

Equations solver categories